2022
DOI: 10.1177/20406223221076891
|View full text |Cite
|
Sign up to set email alerts
|

Application of fucoidan as treatment for cardiovascular and cerebrovascular diseases

Abstract: Fucoidan is a marine polysaccharide. In recent years, fucoidan has attracted wide-scale attention from the pharmaceutical industries due to its diverse biological activities such as lipid-lowering, anti-atherosclerosis, and anticoagulation. This review clarifies the pharmacological effects of fucoidan in the treatment of human cardiovascular and cerebrovascular diseases. Fucoidan exerts a hypolipidemic effect by increasing the reverse transport of cholesterol, inhibiting lipid synthesis, reducing lipid accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 104 publications
1
10
0
Order By: Relevance
“…Consistent with this result, of the two main components we tested, only fucoidan showed significant eGC protection. Designated as HS mimetic [ 32 ], numerous properties with potential for therapeutic application (among others, antithrombotic and anti-inflammatory effects) have been attributed to this compound [ 41 ]. Many years ago, fucoidan was described as a heparinase inhibitor in a tumor model [ 42 ], and this property has since been demonstrated in several other models [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this result, of the two main components we tested, only fucoidan showed significant eGC protection. Designated as HS mimetic [ 32 ], numerous properties with potential for therapeutic application (among others, antithrombotic and anti-inflammatory effects) have been attributed to this compound [ 41 ]. Many years ago, fucoidan was described as a heparinase inhibitor in a tumor model [ 42 ], and this property has since been demonstrated in several other models [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the lack of targeted therapy or prevention options, progress in this field is of great importance. In this regard, fucoidan has become of increasing interest in recent years [ 41 ]. Our present data suggest that part of its antiatherosclerotic effects might be due to the protection of the eGC.…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidan and deep-sea water (DSW) are marine resources that have attracted much attention in recent years. Fucoidan is a unique polysaccharide in brown algae, and numerous studies have suggested that fucoidan exerts multiple biological effects, such as hypoglycemic, lipid-lowering, anticoagulation, antitumor, and antiviral activities [ 2 , 3 , 4 ]. DSW refers to seawater more than 200 m deep [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 40 , 41 These substances were formed via α-1,3-glycosidic, α-1,4-glycosidic, β-1,3-glycosidic, and β-1,4-glycosidic bonds and have great potential in applications in tissue engineering, biomedicine, drug delivery, food, and so on. 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 …”
Section: Introductionmentioning
confidence: 99%
“… 26 Cardiovascular diseases Wang et al. 27 Anticoagulant Shanthi et al. 28 Carrageenan sulfated D-galactose α-1, 4-GB β-1, 3-GB Tissue engineering Jafari et al.…”
Section: Introductionmentioning
confidence: 99%